Diagnostic value of aldosterone to renin ratio calculated by plasma renin activity or plasma renin concentration in primary aldosteronism: a meta-analysis. Issue 6 (20th March 2022) - Liu, Zhenjie; Deng, Xiaohong; Luo, Li; Li, Shaopeng; Li, Man; Deng, Qinqin; Zhong, Weiguo; Luo, Qiang
Abstract: Background: Since the diagnostic value of aldosterone to renin ratio (ARR) calculated by plasma renin concentration (PRC) or plasma renin activity (PRA) is still inconclusive, we conducted a meta-analysis by systematically reviewing relevant literature to explore the difference in the diagnostic efficacy of ARR calculated by PRC or PRA, so as to provide guidance for clinical diagnosis. Methods: We searched PubMed, Embase, and Cochrane Library from the establishment of the database to March 2021. We included studies that report the true positive, false positive, true negative, and false negative values for the diagnosis of primary aldosteronism, and we excluded duplicate publications, research without full text, incomplete information, or inability to conduct data extraction, animal experiments, reviews, and systematic reviews. STATA 15.1 was used to analyze the data. Results: The pooled results showed that ARR (plasma aldosterone concentration [PAC]/PRC) had a sensitivity of 0.82 (95% confidence interval [CI]: 0.78–0.86), a specificity of 0.94 (95% CI: 0.92–0.95), a positive-likelihood ratio (LR) of 12.77 (95% CI: 7.04–23.73), a negative LR of 0.11 (95% CI: 0.07–0.17), and symmetric area under the curve (SAUC) of 0.982, respectively. Furthermore, the diagnostic odds ratio (DOR) of ARR (PAC/PRC) was 180.21. Additionally, the pooled results showed that ARR (PAC/PRA) had a sensitivity of 0.91 (95% CI: 0.86–0.95), a specificity of 0.91 (95% CI: 0.90–0.93), a positive LR of 7.30 (95% CI: 2.99–17.99), a negative LR of 0.10 (95% CI: 0.04–0.26), and SAUC of 0.976, respectively. The DOR of ARR (PAC/PRA) was 155.52. Additionally, we conducted a subgroup analysis for the different thresholds (<35 or ≥35) of PAC/PRC. The results showed that the DOR of the cut-off ≥35 groups was higher than the cut-off <35 groups (DOR = 340.15, 95% CI: 38.32–3019.66; DOR = 116.40, 95% CI = 23.28–581.92). Conclusions: The research results suggest that the determination of ARR (PAC/PRC) and ARR (PAC/PRA) was all effective screening tools for PA. The diagnostic accuracy and diagnostic value of ARR (PAC/PRC) are higher than ARR (PAC/PRA). In addition, within a certain range, the higher the threshold, the better the diagnostic value.